Shifting the 'goal posts': Optimizing the allocation of competition points for sporting contests - Winchester, N. (Journal of Quantitative Analysis in Sports, 2008)
Competition points are awarded in sports tournaments to determine which participants qualify for the playoffs or to identify a champion. We use competition points to measure strength in a prediction model and choose points to maximize prediction accuracy. This allows us to determine the allocation of competition points that most appropriately rewards strong teams. Our analysis focuses on Super Rugby, as the characteristics of this competition closely match our modelling assumptions. We find that the current allocation of competition points does not ensure that the strongest teams qualify for the playoffs and suggest an alternative. Our findings have implications for other competitions.